INTERCONNECTIVY BETWEEN THE CURRICULUM AND THE STUDENTS' EXPERIENCES - Cecilia Titiek Murniati (Celt: A Journal of Culture, English Language Teaching & Literature, 2012)
One of the responsibilities of higher educational institutions is to enhance students' character building and soft skills. The disjuncture between institutions' expectation in educating their students and students' perceptions on the benefit of their teaching and learning processes necessitates a paradigm shift in the college curriculum. Given that universities prepare students to be an individual and a member of a society, college curriculum, therefore, should enhance students' experience both academically and nonacademically. This paper attempts to propose a modest and brief preliminary proposal for curricular change for English Departments in Indonesia. The proposal includes the proposal for five elements of curricular revision - purpose, learner, content, instructional processes, and evaluation and assessment.